Blood Pressure Changes After a Health Promotion Program Among Mexican Workers - Garcia-Rojas, Isabel J.; Omidakhsh, Negar; Arah, Onyebuchi A.; Krause, Niklas (Frontiers in Public Health, 2021)
Background: Cardiovascular disease is becoming increasingly prevalent in low and middle-income countries (LMIC), and high blood pressure (BP) is one of the main risk factors. The efficacy and sustainability of worksite health promotion (WHP) programs for BP reduction in LMIC have yet to be determined. Methods: This non-randomized company-based trial evaluated 6-months and 12-month effects of a WHP intervention on BP among 2,002 participating workers from seven Mexican companies. Intervention and control groups were assigned at the company level. The intervention included nutrition counseling, physical exercise, and stress management components. Mixed models assessed differences in BP change between intervention and control companies in intent-to-treat (ITT), per-protocol (PerP), and as-treated (AsTr) analyses, and also within-group changes stratified by company, intervention component, and baseline cardiovascular risk factor levels. All analyses were adjusted for potential confounders. We accounted for missing data and loss to follow-up using inverse probability of (non-)censoring weighting. Results: ITT analyses revealed mean BP change differences of -1.1 mmHg at 12 months (95% CI: -2.9; 0.6) in intervention companies relative to control companies. PerP and AsTr analyses confirmed this finding. Within-group analyses showed consistent BP reductions at both 6 and 12 months. Substantial differences in BP changes ranging from diastolic -6.1 mmHg, (95% CI: -11.2; -1.2) to systolic -13.0 mmHg (95% CI: -16.0; -10.1) were found among individuals with diabetes at baseline in intervention companies relative to control companies. Conclusion: After 1 year, WHP was associated with modest but uncertain BP reductions. Substantial reductions were mainly observed among diabetic workers.